DISTRIBUSI DAN KONTRIBUSI TENAGA KERJA DALAM KELUARGA TERHADAP PENGELOLAAN AGROFORESTRI DI HUTAN KEMASYARAKATAN, KABUPATEN LAMPUNG BARAT - Dita Cahya Melati; Christine Wulandari (Lambung Mangkurat University-Indonesia, 2021)
Agroforestry is a land management system developed in the Bina Wana Community of Forest (HKm). Agroforestri in Community forest land is the main source of livelihood for communities around the forest. Labor is a resource that can affect the quality and quantity of forest product production, so it needs to be managed well in supporting agroforestry management in HKm. The purpose of this study was to analyze the distribution and contribution of outpoured labor in the family for each agroforestry activity in Gapoktan HKm Bina Wana. The data collection method was conducted by survey using interviews using questionnaires to 24 Gapoktan members. Data analysis was carried out by tabulation for all purposes in this study. The results showed that the distribution of labor outflows was most abundant in harvesting and postharvesting activities, namely 23% of the total use of labor for all agroforestry management activities. Subsequent sequences were soil cultivation (19.09%), planting (14.33%), fertilizing (13.26%), weeding (18.77%), and spraying (10.56%). Total of use of labor is 68% which is included in workers outside of the family. The contribution labor in the family towards agroforestry management in HKm Bina Wana shows a percentage of 32% of total workforce used.